Pro tools 101 official courseware - Digidesign ([S.l.] : Course Technology PTR, 2006)
Recording enthusiasts-from hobbyists to aspiring professionals hoping to work in the recording, live sound, or post-production industries-should buy this book if they want to learn Pro Tools in the way that the manufacturer, Digidesign, recommends. Pro Tools 101 is the best first step-the official first step-for anyone embarking on the Pro Tools learning curve. Pro Tools 101 is used in Digidesign's own training and certification programs. The book's many exercises, enhanced by its sample sessions and source files, allow readers who may have never used the software before to get up and running on all the fundamental operations, including creating a session, recording audio and MIDI, basic editing and mixing techniques, and burning songs to CD.